2011
DOI: 10.1103/physreve.84.015201
|View full text |Cite
|
Sign up to set email alerts
|

Chimera states are chaotic transients

Abstract: Spatiotemporal chaos and turbulence are universal concepts for the explanation of irregular behavior in various physical systems. Recently, a remarkable new phenomenon, called "chimera states," has been described, where in a spatially homogeneous system, regions of irregular incoherent motion coexist with regular synchronized motion, forming a self-organized pattern in a population of nonlocally coupled oscillators. Whereas most previous studies of chimera states focused their attention on the case of large nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

21
307
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 268 publications
(339 citation statements)
references
References 35 publications
21
307
6
Order By: Relevance
“…They have been the subject of intensive theoretical investigations, e.g. [4][5][6][7][8][9][10][11][12][13][14][15]. Experimental evidence of chimeras has only recently been provided for optical [16], chemical [17], mechanical [18] and electronic [19] systems.…”
mentioning
confidence: 99%
“…They have been the subject of intensive theoretical investigations, e.g. [4][5][6][7][8][9][10][11][12][13][14][15]. Experimental evidence of chimeras has only recently been provided for optical [16], chemical [17], mechanical [18] and electronic [19] systems.…”
mentioning
confidence: 99%
“…Classical chimera states have a dynamical character, however they have a long life duration. They correspond then to a metastable regime (until the collapses studied in [5] for finite size chains) and not to a short life transient regime. Moreover for some classical models of infinite chains [1], the classical chimera states present an infinite life duration and correspond to a permanent regime.…”
Section: Quantum Chimera Statesmentioning
confidence: 96%
“…This behaviour is in accordance with the Poisson distribution of the LSD which is not characteristic to a quantum chaotic behaviour but to a quantum pseudorandom behaviour. In comparison with the classical case, if the model (1) presents chimera states which are always transient chaotic as shown in [5], the main characteristic of the classical chimera states are the coexistence of ordered and disordered dynamics in the same chain. The disordered dynamics is not necessary chaotic.…”
Section: Chaotic Behaviourmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the stability of chimera states in finitely discretized systems is questioned. In fact, it is reported that when N is finite, chimera states with the sine coupling are chaotic transient and finally collapse into the completely synchronous solution [12,13,26]. Recently, Ashwin and Burylko proposed the weak chimera similar to the chimera state, which is defined by the coexistence of frequency-synchronous and -asynchronous oscillators in the systems of coupled indistinguishable phase oscillators but is not necessarily spatially structured as coherent and incoherent domains [28].…”
mentioning
confidence: 99%